Solos com caráter coeso:limitações do espaço poroso livre de água no desenvolvimento vegetativo do milho - Marques, Edilaine da Silva (2019)
Soils with a cohesive character, due to their physical characteristics, can cause limitations to the cultivation of plants. These limitations are mainly associated with a greater physical impediment to the penetration of roots, as well as with a greater difficulty in absorbing water by plants when the soil is under greater aeration porosities. However, in conditions of low aeration porosities, there may be restrictions in the gas exchange processes. Considering this context, it was hypothesized that horizons with a cohesive character, in the moisture that the soil has not yet reached a hard to extremely hard consistency, may present aeration porosities that affect the vegetative development of plants. Thus, the objective was to know the influence of the horizon with a cohesive character, maintained in humidity conditions with different aeration porosities, in the development of maize plants. The experiment was carried out in Fortaleza-CE, in a randomized block design, with five aeration porosities (PA) (0.04; 0.06; 0.09; 0.11 and 0.13 cm3 cm-3) and six repetitions. Each experimental unit was composed of one plant per pot with 40 cm (20 cm horizon A and 20 cm horizon B with a cohesive character). The variables analyzed were: intrinsic permeability from soil to air (Kar); gas exchanges and biometric variables; and nutritional ones. Additions to PA provided an increase in Kar. The PA of 0.04 and 0.13 cm3 cm-3 provided lower photosynthetic rates (A), with 24.54 and 25.50 μmol CO2 m2 s-1, respectively; lower internal CO2 concentration with 140.72 and 118.66 μmol mol-1, respectively; smaller diameter (24.22 and 24.19 mm, respectively) and stem length (57.5 and 52.5 cm, respectively); the limitations in the lowest PA are related to the state of hypoxia in the soil and in the highest PA, linked to the mild water deficit. Stomatal conductance (0.158 mol H2O m-2 s-1), transpiration (4.77 mmol H2O m2 s-1) and nitrogen (17.6 g kg-1) and potassium (23.6 g kg-1) were lower in the largest PA. The dry mass of roots in the horizon A and B with a cohesive character was lower in the lowest PA (18 and 11.9 g, respectively). It was concluded that the PA of 0.04 cm3 cm-3 reduced the development of the maize plant, due to the condition of hypoxia of the soil. On the other hand, the PA 0.13 cm3 cm-3, there was a reduction in the A and in the stem length and diameter variables, these linked to the slight water deficit in the soil. The intermediate PA range showed the highest photosynthetic rates, largest diameters and stem length in relation to extreme treatments.